Comparing available JAK inhibitors for treating patients with psoriasis. (4th March 2022) - Funk, Parker J.; Perche, Patrick O.; Singh, Rohan; Kelly, Katherine A.; Feldman, Steven R.
ABSTRACT: Introduction: Cytokine blockers have revolutionized the management of psoriasis. While efficacious, not all patients respond, and treatment may lose efficacy over time. Janus kinase (JAK) inhibitors target the Janus Kinase/Signal Transducer and Activator of Transcription (JAK/STAT) transduction cascade from transmitting cytokine signals in psoriasis. Areas covered: A PubMed search of phase I, II, and III clinical trials published between 2012 and 2021 utilizing the key terms: Janus kinase and psoriasis . Our search was expanded from clinical trials to further investigate the pathophysiology, standard of care, and safety and efficacy of JAK inhibitors in psoriasis. Expert opinion: Current treatments for psoriasis include topicals, phototherapy, and systemic therapy. The subcutaneous or intravenous route of biologic administration presents a challenge as patients often prefer oral medications over injections and because of anti-drug antibody development. Tofacitinib is effective and has an overall mild-to-moderate safety profile but includes an FDA black box warning for increased risk of cardiovascular events and malignancy. Other JAK inhibitors have an acceptable safety profile and are effective in early clinical trials. Poor topical medication adherence should be considered when evaluating JAK inhibitors. Oral JAK inhibitors may provide a preferable route of administration and improved clinical outcomes.